Dialogic Consensus in Medicine—A Justification Claim. Issue 1 (22nd December 2018) - Walker, Paul; Lovat, Terence
Abstract: The historical emphasis of medical ethics, based on substantive frameworks and principles derived from them, is no longer seen as sufficiently sensitive to the moral pluralism characteristic of our current era. We argue that moral decision-making in clinical situations is more properly derived from a process of dialogic consensus. This process entails an inclusive, noncoercive, and self-reflective dialogue within the community affected. In order to justify this approach, we make two claims—the first epistemic, and the second normative. The epistemic claim follows from Habermas' "ways" of knowing. We argue that the dialogue emanating from this episteme focuses on the relevant facts about the patient, as well as on the values attached to these facts, thus allowing facts and their meanings to serve as the basis for reflective action appropriate to the circumstances. The normative claim follows from Habermas' discourse theory of morality and communicative action. It determines that clinical decision-making should be approached from the perspective of the actual reality of people in their situation of illness, set in their socio-cultural background, and hence be grounded in the second-person perspective. Relocating ethical decision-making from a monological space into one characterized by dialogue is especially appropriate to the clinical encounter.